Platelet Satellitism in a Patient with Bronchial Asthma - Koju, S.; Vaidhya, N.; Twitwi, R.; Shankhadev, R.; Pote, N. (Kathmandu University Medical Journal, 2022)
Platelet satellitism is uncommon phenomenon characterized by formation of platelet rosette around polymorphonuclear leucocytes in blood smear prepared from Ethylenediaminetetraacetic acid anticoagulated blood. This phenomenon may cause reporting of spurious thrombocytopenia unless proper examination of blood smears. Here we describe a case of platelet satellitism in a 29 year old female which has been incidentally found on evaluation of eosinophilia in a bronchial asthma patient.